Hydrogen Permeation Through Fluoride Molten Salt Mixed with Ti Powder. (17th November 2017) - Nishiumi, Ryosuke; Fukada, Satoshi; Yamashita, Jun; Katayama, Kazunari; Sagara, Akio; Yagi, Juro
Abstract: H2 permeation behavior in a new molten salt of Flibe mixed with 0.5 wt% Ti powder is experimentally and analytically investigated. Ti powder included in Flibe can suppress H2 permeation for 70 hours lower than the H2 detection limit after the start of experiment. H2 diffusion behavior in the Flibe+Ti system is analyzed using an unsteady-diffusion equation. The time delay of overall H2 diffusion in the Flibe+Ti system is over 200 times larger than that in Flibe. The effective diffusivity and solubility in the Flibe+Ti system are determined from fitting the analytical solution to experimental H2 permeation rates.